Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Hello I have following problem: solve equation $\log{(x-5)^2}+\log{(x+6)^2}=2$

and I rewrited this equation as

$2\log{(x-5)}+2\log{(x+6)}=\log{100} \implies 2(\log{(x-5)(x+6))=\log{100}} \implies \log{x^2+x-30}=\log10 \implies x^2+x-40=0 $

and I solved this equation, but I obtained only two solutions and there should be four, so I wonder if it is necessary to create $\log{(x-5)^2(x+6)^2}=\log{100}$ or is a simplier way.

share|improve this question
    
I assume the question specifies the base of log is $10$? –  Macavity Dec 1 '13 at 15:15
    
yes of course . –  Mark Dec 1 '13 at 15:16

2 Answers 2

up vote 2 down vote accepted

$$\log{(x-5)^2}+\log{(x+6)^2}=2$$ $$\log{((x-5)(x+6))^2}=2$$ $$((x-5)(x+6))^2=10^2=100$$ $$(x-5)(x+6)=\pm10$$Solve from here

share|improve this answer

As the logarithm term contains squares, we can allow $x-5,x+6$ to be negative

In fact, $\log b^2=2\log |b|$ for real $b$

As $\log A+\log B=\log (AB),$

$$\implies \log_{10}\{(x-5)(x+6)\}^2=2$$

$$\implies \{(x-5)(x+6)\}^2=10^2=100$$

$$\implies (x-5)(x+6)=\pm10$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.